A multivariate analysis after preservation rhinoplasty (PR) – a prospective study. Issue 1 (January 2022) - Stergiou, Georges; Fortuny, Clara Guardiola; Schweigler, Adrian; Finocchi, Valerio; Saban, Yves; Tremp, Mathias
Summary: Background: Preservation rhinoplasty (PR) is considered to be an innovative approach with high patient satisfaction. However, little is known about its functional outcomes and radiological analyses. Patients and Methods: In this prospective clinical study, 30 patients (20 female and 10 male patients, mean age 30.7 ±9.8 years) were operated on between 2017 and 2021. Radiological assessment was evaluated by cone beam computed tomography before surgery and at final follow-up. Patient assessment regarding their outcome was assessed at final follow-up using a validated questionnaire (rhinoplasty outcomes evaluation questionnaire = ROE). Results: After a mean follow-up of 8.4 ± 5 months (range = 1 – 18 months), radiological analyses denoted an overall improved internal nasal valve (INV) angle after surgery (preoperative = 20.77° ± 3.2° vs. postoperative = 21.82° ± 5.7°, p  = 0.18). Those results are in accordance with an overall high patient satisfaction for both function and aesthetics (ROE score 18.4 ± 4.3). Conclusion: Our study showed a preserved and widened INV angle after PR, along with high patient satisfaction. Level of Evidence: III